2010
DOI: 10.1002/esp.1926
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and residence time of suspended sediment stored within the channel margins of a gravel‐bed bedrock river

Abstract: Previously undocumented deposits are described that store suspended sediment in gravel-bedded rivers, termed 'fi ne-grained channel margin' (FGCM) deposits. FGCM deposits consist of sand, silt, clay, and organic matter that accumulate behind large woody debris (LWD) along the margins of the wetted perimeter of the single-thread, gravel-bed South River in Virginia. These deposits store a total mass equivalent to 17% to 43% of the annual suspended sediment load. Radiocarbon, 210 Pb and 137 C dating indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 51 publications
3
75
0
Order By: Relevance
“…Thus, our findings are consistent with previous results (Walling et al, 1998;Trimble, 1999;Hupp et al, 2010Hupp et al, , 2013Skalak and Pizzuto, 2010;Smith et al, 2011). Extrapolations suggested that within the drainage network, sediment contributions per meter of channel length were greater for larger streams, but the majority (41%-62%) of cumulative streambank sediment loads were from first-and second-order tributaries.…”
Section: Discussionsupporting
confidence: 96%
“…Thus, our findings are consistent with previous results (Walling et al, 1998;Trimble, 1999;Hupp et al, 2010Hupp et al, , 2013Skalak and Pizzuto, 2010;Smith et al, 2011). Extrapolations suggested that within the drainage network, sediment contributions per meter of channel length were greater for larger streams, but the majority (41%-62%) of cumulative streambank sediment loads were from first-and second-order tributaries.…”
Section: Discussionsupporting
confidence: 96%
“…We demonstrate that these zones, even in low-order streams, may sequester significant quantities of fine particulate material, contaminants, and nutrients (33). The continuous processes of fluvial redistribution in small catchments are, in turn, important in supplying organic material (34,35,36) and soil carbon (37,38) to larger river systems, lakes, wetlands, and estuaries (39,40).…”
Section: Resultsmentioning
confidence: 86%
“…A number of factors contribute to the spiraling of particulates, notably the particle size, flow velocity, channel depth, and Fe or Mn fingerprint of channel sediments (Whiting, Matisoff, Fornes, & Soster, ). The high‐energy flows created by dam releases (Csiki & Rhoads, ) and pool‐riffle sequences reach provide an environment for erosion, entrainment, and reworking of the suspended particulates (Hupp et al, ; Sear, ; Skalak & Pizzuto, ). Whiting et al, () examined the transport of suspended sediment in an upland river with flow characteristics similar to the Roanoke River and found that the transport distance of suspended particulates could be as short as 3 km due to the presence of pools along the flowpath.…”
Section: Discussionmentioning
confidence: 99%